Efficient callus induction and regeneration of tea plant (Camellia sinensis) - Zhang, Xin-lei; Lu, Mi; Li, Meng; Zhang, Hong-meng; Yu, Longfeng; Wu, Tian (Scientific reports, 2025)
Tea, one of the world’s three major non-alcoholic beverages, sustains enormous annual consumption globally. However, the growth and development time of tea trees is long, the planting is affected by time and region, and it is not conducive to the diversification and innovation of tea varieties. To establish an efficient in vitro regeneration system for tea plant, the effects of culture conditions and plant growth regulators (PGRs) on adventitious bud differentiation and rooting were investigated in this study. The large-leaf tea variety ‘Yunkang 10’ was used for explant collection and the MS (Murashige and Skoog) medium was adopted as the basal medium. Callus induction peaked at 100% on the MS medium supplemented with 3.0 mg/L 6-benzylaminopurine (BAP) and 0.2 mg/L naphthaleneacetic acid (NAA). Optimal subculture occurred on MS + 3.0 mg/L BAP + 0.3 mg/L NAA + 3.0 mg/L gibberellic acid (GA 3 ), while maximal proliferation (> 300% increase) used MS + 0.2 mg/L BAP + 0.1 mg/L NAA + 3.0 mg/L GA 3 . Nine-month-old calli showed highest bud differentiation (24.73% per callus) on MS + 2.0 mg/L BAP + 0.2 mg/L NAA and adventitious bud proliferation reached 89.64% on MS + 1.5 mg/L BAP + 0.1 mg/L NAA. Paraffin sectioning of calli at different stages confirmed adventitious bud origin. For the rooting induction rate, it peaked at 78.56% on 1/8 MS + 3.0 mg/L indole-3-butyric acid (IBA). Then the tissue cultured seedlings were moved into the field, and the transplantation using soil: humus: perlite = 6:3:1 achieved 71.11% survival. Further Start Codon Targeted (SCoT) marker analysis confirmed the genetic fidelity in the regenerated tea plants. The optimized system developed here enhances tea propagation and supports future genetic engineering efforts.